2007
DOI: 10.1007/s10297-006-0077-1
|View full text |Cite
|
Sign up to set email alerts
|

Communication techniques and coding for atmospheric turbulence channels

Abstract: In free-space optical communication links, atmospheric turbulence causes fluctuations in both the intensity and the phase of the received light signal, impairing link performance. In this paper, we describe several communication techniques to mitigate turbulence-induced intensity fluctuations, i.e., signal fading. These techniques are applicable in the regime in which the receiver aperture is smaller than the correlation length of the fading, and the observation interval is shorter than the correlation time of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…It has been shown that the optical channel from LEO to ground is characterized by long fades on the order of milliseconds that result in burst errors for the data. 22,72,93,94 These burst errors cause multiple correlated errors in one codeword, and the fades are long enough such that the number of errors in one codeword will exceed the error correcting capabilities of the code. Linear block codes, such as RS codes, do not perform well in the presence of burst errors because entire codewords may be lost.…”
Section: Waveform Coding and Interleavingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the optical channel from LEO to ground is characterized by long fades on the order of milliseconds that result in burst errors for the data. 22,72,93,94 These burst errors cause multiple correlated errors in one codeword, and the fades are long enough such that the number of errors in one codeword will exceed the error correcting capabilities of the code. Linear block codes, such as RS codes, do not perform well in the presence of burst errors because entire codewords may be lost.…”
Section: Waveform Coding and Interleavingmentioning
confidence: 99%
“…55 (11) fades when paired with forward error correction, and for this reason, NODE will use a block interleaver. 22,72,93,94 We chose a fade depth of 1 s since a common design practice for interleavers is to have the depth of the interleaver be 100 to 1000 times the coherence time of the channel fading process, which, as stated earlier, is on the order of milliseconds. Since NODE will use PPM orders of 16, 32, 64, and 128, the modulator will encode 4, 5, 6, and 7 bits per PPM symbol, respectively.…”
Section: Measurementioning
confidence: 99%
“…These fluctuations become stronger with the appearance of multipath propagation and random caustics [8]. Such conditions increase the risks of failures in high-speed communication systems at optical and millimeter frequencies [2,9,10]. The main remedy for fading is a diversity reception [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…When a wave propagates in inhomogeneous media such as a turbulent atmosphere or the ionosphere, focusing and defocusing induce wave amplitude fluctuations which are often referred to as fading or amplitude scintillations [2,3]. The literature on theoretical and experimental investigations into scintillations is already quite voluminous (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Each WDM channel has a specific center frequency or signal spectral, which is at a 100 GHz spacing (ITU-T G.694.1). For WDM channels that are propagated through atmospheric turbulence, and hence are based on the fourth order of the strong fluctuation theory, each signal spectral modulates noise (Prasad, 2005;Zhu et al, 2007;Weyrauch, 2007). Thus, maximum noise is accumulated depending on the scale of turbulence and optical link distance on the WDM of the FSO.…”
Section: Introductionmentioning
confidence: 99%